Attitude towards the use of learning management system among university students: A case study - A.Trayek, Fuad A.; Syed Hassan, Sharifah Sariah (Anadolu University, 2013)
Learning management system (LMS) is a learning platform for both full time and distant learning students at the International Islamic University in Malaysia (IIUM). LMS becomes a tool for IIUM to disseminate information and learning resources to the students. The objectives of this study were to investigate students' attitudes toward the use of LMS, to verify the impact of perceived usefulness and perceived ease of use on attitude towards use of learning management system, to examine the differences in attitudes toward the use of LMS between distance learning and full time students. There were 120 (70 full time and 50 distance learning) students at the Institute of Education responded for the study. The collected data was analysed using descriptive statistics, t-test and Multiple Regression Analysis (MRA). The results of the study showed that perceived ease of use and perceived usefulness determine students' attitudes toward the use of LMS. However, this study did not find any significant differences between distance learning and full time students. According to the findings the study recommended that the University should continue using LMS because it is useful for both distance learning and full time students. Further suggestions are made to customize and upgrade the LMS suitable for innovative teaching and learning.